Ḥukm bi-mā anzala'llāh: The Forgotten Prehistory of an Islamist Slogan. Issue 1 (February 2016) - Wagner, Mark S.
Abstract : The phrases ḥukm bi-mā anzala'llāh ('ruling/judging by that which God has revealed') and ḥukm bi-ghayri mā anzala'llāh ('ruling/judging by other than that which God has revealed') as well as the identities of the kāfirūn, ẓālimūn, and fāsiqūn guilty of the latter have preoccupied Muslim exegetes of Sūrat al-Māʾida, verses 42–8. Among Muʿtazilīs, the verses pointed to the instrumentality of revelation, including that of the Muslims, an idea that some Twelver Shīʿī exegetes preserved. Among Sunnīs, the verses referred specifically to the ideal interaction between Muslim and non-Muslim legal systems. This article will explore how Rashīd Riḍā laid the groundwork for the Islamist appropriation of these verses by taking Twelver Shīʿī exegesis of the verses out of its original context. The religious debate following the assassination of Anwar Sadat dramatised the clash between the traditional Sunnī understanding of the verses and the novel interpretation offered by Riḍā and later Islamist exegetes such as Shaʿrāwī and Quṭb.